Compositional, electrical and thermal properties of nonstoichiometric titanium oxide thin films for MEMS bolometer applications. (September 2022) - Yadav, Isha; Jain, Surbhi; Joshi, Shalik Ram; Goyal, Anshu; Tomar, Monika; Gupta, Sudha; Dutta, Shankar; Chatterjee, Ratnamala
Abstract: Nonstoichiometric titanium-oxide (TiOx) films are being extensively studied for MEMS bolometer applications. To have superior bolometer performance, the TiOx layers should have a high value of temperature coefficient of resistivity (TCR) and a low value of thermal conductivity. This paper presents the evolution of the electrical and thermal properties of RF sputtered TiOx films with the film thickness and stoichiometry. A series of amorphous TiOx films of 100 nm, 200 nm, and 400 nm thickness are deposited with different oxygen flow rates. X-ray photoelectron spectroscopy (XPS) study revealed the presence of only Ti 4+ and Ti 3+ oxidation states in the deposited films, and no TiO phase exists (no Ti 2+ state). The oxygen-titanium atomic ratios (O/Ti) of the films are 1.5, 1.7, and 1.9. The TCR of the films is increased (from -1.1 %/K to -4.8%/K) with the increased oxygen content. The cross-plane thermal conductivities of the films are by the 3-ω technique. The thermal conductivity of the TiOx films is increased (0.5 W/m-K to 2.4 W/m-K) with the increase in film thickness and is independent of its 'x' values. Characteristics of MEMS bolometer pixel (17 mm pitch) are simulated based on the measured properties of the TiOx films. The film having 2.75 %/K TCR and 1.12 W/m-K thermal conductivity, exhibited minimum NETD (37.3 mK) with decent voltage responsivity (1.62x10 6 V/W). Highlights: Growth of amorphous TiOx films (100–400 nm thick) by reactive sputtering. Compositional analysis showed variation of O/Ti atomic ratio ( x) from 1.5 to 1.9. Films TCR (1.1–4.8 %/K) rises with ' x ' and is thickness independent. Thermal conductivity of the TiOx films (0.5–2.4 W/m-K) are lower than TiO2 . Simulated bolometer pixel characteristics based on the measured TiOx properties.